Tribhuvan University in Kirtipur; A History of Resistance and Change (Patan Prospective Journal, 2023)
This paper, focused on the history of establishment of university in Kiritpur, is centered around a question - How the establishment of Tribhuvan University in Kirtipur is associated with a pattern of change influencing the everyday life of the local people? Given the background, this paper has intended to  shed light on the history of Tribhuvan University in Kirtipur amidst resistance of the people, particularly on how the process of establishment of the university proceeded at the beginning and, in addition, the impacts on the society and the people of Kirtipur following the founding of a great institution in the history of Nepal. For this purpose, qualitative information has been generated from ethnographic interviews supplemented by focus group discussion guided by a check-list, mainly with the local senior citizen informants above 60 years of age who have witnessed the place and processes from decades. The study shows that the people who were reluctant to welcome the university because it forcefully purchased their land and they were compelled to shift from farming to non-farming occupation had lots of grievances and dissatisfaction with the government. However, over time the urbanization, expansion of market and emigration of the population have found to have brought various aspects of development regarding road and transportation, modern housing and settlement, growth in physical infrastructures associated with education, health and market. Now, people have realized the benefit directly and indirectly in their lives.